MORFOLOGI DAN EFISIENSI SEL SURYA FOTOELEKTROKIMIA BERBASIS NANOSTRUKTUR ZnO DILAPISI TEMBAGA - Iwantono Iwantono; Sella Natalia; Rinaldo Abdi; Awitdrus Awitdrus; Zulkarnain Zulkarnain (Komunikasi Fisika Indonesia, 2018)
ZnO nanostructures coated Cu (Copper) have been successfully grown using a method of seed mediated hydrotermal. The growth of Cu coated ZnO nanostructures were used as an active material of DSSC. The Cu on ZnO nanostructures has been coated at a concentration of 10 mM at room temperature in 30 minutes. The samples were characterized using Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-ray (EDX). The FESEM images showed that the geometrical shape of ZnO nanostructures was nanoflower. Spectra of EDX showed Cu was really exist in all samplesof about 0.8%. A DSSC was fabricated by using the ZnO nanostructured coated Cu as an active material.The results of I-V measurements under iluminattion of halogen lamp its intensity of 100 mW/cm2 has produced efficiency 0.35% (DSSC without copper) and increasedto 0,43% whenCuwas coated on ZnO.